Business Ethics in the Social Context - Newton, Lisa. author. aut Link
X, 100 p.
Keywords: The book tracks the rise of Business Ethics as a discipline in the United States through a review of the basic understandings of the role of business practices in the operations of society, beginning with Aristotle and proceeding to a review of the formative concepts and cases in the history of American business.